The Setup Model Farm Machinery and Uquipment for Up Land Sugar Cane Industry - Sigit Prabawa; Bambang Pramudya; Moeljarno Djojomartono; M.A Chozin (Jurnal Keteknikan Pertanian, 2000)
The objective of the research is to build the setup model of farmmachinery and equipment for zip land sugar cane indzlstry. From this model can be determined: (I) selection of farm machinery/equipment, (2)number farm machinery/equipment, and (3) optitnun? longevrty of ratoon.The result shows that the technolog?, consideration hus been the priniary consideration on farm tnachinery and eqztipnzent selection. The next is econonzy consideration. The attention for social and environment consideration is poor.